PENERAPAN TEKNOLOGI INSEMINASI BUATAN MENGGUNAKAN SEMEN SEXING BAGI PETERNAK BREEDING SAPI DI SIDOMULYO MERAUKE - Nurcholis, Nurcholis; Sumaryanti, Lilik; Salamony, Syetiel Maya (Universitas Mataram, 2025)
Cattle breeders in Merauke are generally still on a traditional scale with low livestock productivity. The application of reproductive technology in the form of artificial insemination provides opportunities and hope for breeders to improve cattle quality. Currently, cattle breeding cannot be appropriately implemented due to the low availability of superior bulls. In addition, breeders prefer cattle offspring with the sex they desire (male or female), which has not been realised. Therefore, the purpose of community service for cattle breeders in Merauke is to implement research results in the form of semen sexing technology. The use of semen sexing can help breeders determine livestock goals. The extension method and application of artificial insemination using semen sexing was carried out by involving 4 groups of breeders in Merauke, with a total of 40 breeders. The results of the breeder's skills after participating in training and mentoring on estrus detection reached 83.07%. The application of artificial insemination using semen sexing received a response of 97.5% very satisfied, and 2.5% satisfied response. The success of AI reached 88.76%. The conclusion is that the implementation of artificial insemination has a positive and beneficial impact on cattle farming groups in Merauke.